MORPHOLOGY OF Patchouli OIL MICROCACULES (Pogostemon cablin Benth) WHICH IS ENKAPSULATED USING CHITOSAN - Kleriyani Mayan; Arrijani; Emma Moko (Indonesian Biodiversity Journal, 2020)
Patchouli oil (Pogostemon calbin Benth) has economic benefits which are widely used as raw material for the pharmaceutical, perfume and food industries. Although widely used in various fields, patchouli oil or essential oils are generally young to evaporate, are susceptible to high temperatures and humidity, so we need a way / solution to overcome this, one way is encapsulation. Encapsulation is a technique to protect the core material which was originally liquid from becoming a solid / powder form and can protect the core material from losing its taste and aroma. Coating is a material that can mix with the core material, is not reactive to the core material and can form a layer around the core material. Chitosan is a good coating for essential oil encapsulation. This study aims to determine the particle size and microcapsule characteristics of patchouli oil (P.calbin Benth) using chitosan coating. The microcapsules were made using a freeze dryer with the freeze drying method. The dried samples were analyzed for particle size, morphological shape and content using SEM (Scanning Electron Microscopy). The results showed that the samples with a coating material composition of 1:2 were completely dry freeze drying. The average particle size <3.5 µm with a magnification of 10,000x with round morphology and various shapes. Analysis of the chemical content in the sample showed the similarity of the main compounds in patchouli essential oil, namely α-guaiene, azulene, α/β/ γ-patchoulene, seychellene, and α-himachalene and there was the addition of carbon (C) 76.07% and oxygen. (O) 16.46% originating from coating material